Total body fluid is the factor that affects the pharmacokinetics of tolvaptan, and its efficacy, in acute worsening heart failure patients - Takahiro Kato; Yoko Yasuda; Hitomi Okamoto; Yuji Saito; Yusuke Nakano; Katsuhiko Matsuura; Masafumi Oonishi; Tetsuya Amano (Wiley, 2023)
Abstract The optimal starting dose of tolvaptan to effectively improve fluid retention in patients with heart failure (HF) is unknown. This study explored the factors affecting the pharmacokinetics (PKs) and pharmacodynamics of tolvaptan in patients with decompensated HF. We prospectively enrolled patients who were slated to receive tolvaptan because of volume overload associated with chronic HF. Blood samples were collected to measure tolvaptan concentrations before and 4, 8, 12-15, 24, and 144 h after administration. Additionally, demographic parameters, coadministered drugs, and body fluid composition were evaluated. Multiple regression analysis to detect PK parameters for the prediction of body weight (BW) loss at day 7 after the initiation of tolvaptan treatment and PK analysis to explore the factors affecting the PKs of tolvaptan were performed. In total, 165 blood samples were obtained from 37 patients. The predictors of weight loss on day 7 were area under the curve (AUC0-∞) of tolvaptan. PK analysis of the data revealed a strong correlation between CL/F and Vd/F, but no correlation between CL/F and kel (r = .95 and .06, respectively). A significant correlation was observed between total body fluid and Vd/F, and this correlation remained statistically significant even after adjusting for BW (r = .49, p < .05). Fat was also significantly correlated with Vd/F before adjusting for BW, on the other the correlation disappeared after adjusting BW. The optimal dose of tolvaptan based on total body fluid levels in individual patients could result in the alleviation of fluid retention in patients with HF.